PENGARUH PERSONAL SELLING DAN DIRECT MARKETING YANG EFEKTIF UNTUK MENINGKATKAN VOLUME PENJUALAN PAKAIAN ANAK PADA TOKO REZEKI WIJAYA - Hendra; Elisabeth Nainggolan (LPPM STIE EKA PRASETYA, 2020)
The purpose of this study is to determine the effect of Personal Selling and Direct Marketing on Sales Volume at Toko Rezeki Wijaya. Research methodology used is descriptive quantitative method, the unit of analysis in this study is Toko Rezeki Wijaya and its observation unit are customers of Toko Rezeki Wijaya. The population in this study is amount to 65 of Toko Rezeki Wijaya customers. The technique of determining the number of samples used in this study was saturated samples and amounted to 65 respondents. The research method used is by data collection techniques through library research and field research conducted systematically based on research objectives. The analytical method used to solve problems and prove hypotheses is descriptive analysis, regression analysis. This analysis includes validity and reliability, classic assumption test, multiple regression analysis, hypothesis testing through t and F test, and test the coefficient of determination (R2). The t-test results show that the Personal Selling variable has a positive and significant effect on Sales Volume at Toko Rezeki Wijaya and the Direct Marketing variable have a positive and significant effect on Sales Volume at Toko Rezeki Wijaya.